FEMINISME DALAM TASAWUF: SEBUAH TINJAUAN LITERATURE REVIEW - Deni Irawati; Nunu Burhanuddin (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2023)
Islamic feminism seeks to empower women spiritually and morally, eradicate injustice,and promote gender equality in all areas of life. Humans, both men and women, have equal opportunities to obtain maqamat and ahwal in order to reach true Sufis, as stated in Sufism literature. This article aims to find out and understand about feminist thinking in Sufism in the modern era. This article uses a literature review approach. Literature search was carried out online through Google Scholar which was limited from 2012- 2022 with a search process using the keywords "Feminism and Sufism". The results of this research show that feminism is a concept that describes equality between women and men in the social, political and economic fields. Islamic feminists contribute to the production of ideas of egalitarianism and gender activism by placing women centered on their own freedom. There are very few female Sufi names in the history of Sufism because culturally women are often placed in a lower position. In the world of Sufism, the strong influence of culture which is so strict in discriminating people from this aspect of gender, makes the position of women not get a proper space. The impact of the research is expected to be able to answer various challenges for some of the problems that occur in a woman